A systematic review and meta-analysis of the association between serotonergic gene polymorphisms and obstructive sleep apnea syndrome. - Huajun Xu; Jian Guan; Hongliang Yi; Shankai Yin (PLoS ONE, 2014)
Background 5-Hydroxytryptamine receptor (5-HTR) and 5-hydroxytryptamine transporter (5-HTT) gene polymorphisms have been reported to be associated with susceptibility to obstructive sleep apnea syndrome (OSAS). The associations, derived from sporadic, inconsistent, small-sample-size studies, need to be evaluated further in a meta-analysis. Methods Relevant studies were identified by searching PubMed, Embase, The Cochrane Library, China National Knowledge Infrastructure (CNKI), Wanfang, and Weipu. Eligible data were extracted from each included study. Odds ratios (ORs) were calculated using a fixed-effects or a random-effects model. The ORs and 95% confidence interval (CI) were used to assess the strength of the association between serotonergic gene polymorphisms and OSAS in the dominant and recessive models, as well as alleles. The Q statistic was used to evaluate homogeneity and Begg's test was used to assess publication bias. Results Eight studies were finally included in the meta-analysis of the association between 5-HTR2A gene variants (including 102T/C and 1438G/A), 5-HTT gene polymorphisms (including 5-HTT gene-linked promoter region (5-HTTLRP), and serotonin transporter intron 2 variable number tandem repeat (STin2VNTR) and OSAS risk. The G allele of 5-HTR2A 1438G/A, long 5-HTTLPR, and 10-tandem-repeats STin2VNTR were shown to increase OSAS susceptibility, with ORs of 2.33 (A vs. G, 95% CI 1.48-3.66), 1.24 (L vs. S, 95% CI: 1.04-1.49), and 2.87 (10 vs. 12, 95% CI: 1.38-5.97), respectively. These significant differences were determined in both dominant and recessive models. Of the 5-HTR2A 1438G/A gene polymorphism, the AA genotype increased the OSAS risk, with an OR of 4.21 (95% CI: 2.83-6.25) in a recessive model in male OSAS patients, but no significant association was found in females. Conclusions Our meta-analysis demonstrated that polymorphisms in the 5-HTR2A 1438G/A and 5-HTT genes contributed to susceptibility to OSAS. The A allele of the 1438G/A gene polymorphism is predominantly distributed in males and increased the OSAS risk significantly.